Técnicos de Secretaria de Educação atuando como formadores de diretores - Silva, Márcia Cristina da (2017)
Continuing education of school principals has been a challenge for the technical teams of state departments of education, which have faced the need to support these professionals in the work context. Therefore, the problem of this research focuses on the question: how do state department technicians prepare to develop continuing education with school principals? That way, the general objective of the research is to investigate the performance of the technicians of a municipal state department of education as trainers of principals. The theoretical reference aimed to identify recent research related to the themes of training of principals, continuing education within state departments and analysis of training programs of principals. In order to deepen concepts about the relationship between continuing education and professional development and continuing education of school principals, we have used some theoretical references such as Libâneo (2004), Canário (2007), Marcelo (2009), Imbernón (2010), Lück 2000), Vieira and Vidal (2014), Abruccio (2010) and Paro (2015). The field defined for conducting the research was the Municipal State Department of Education of Aracruz, State of Espírito Santo (ES), and the subjects are five technicians who act as responsible for the continuing education of the 53 school principals. For the accomplishment of this research, of qualitative character, individual and collective interviews were carried out. The method for data analysis followed the prose analysis assumptions (ANDRÉ, 1983). The main results obtained were: continuous education has enabled the group of technicians to improve their professional practices and this is due to the constant search to maintain interlocution with more experienced partners, as well as the investment in self-training; And the use of training strategies, such as on-call and visits to priority schools, has fostered greater interaction and exchanges of experience among principals. The main problem faced by the researched team has been the realization of the education of school principals concomitantly to the office of their positions of technicians of a state department that demands actions that overlap. However, these professionals have faced the challenges of being trainers in a reflective and collaborative way, and seeking partnerships that have led them to the ever greater enhancement of the role of school principals trainers